Concordance and determinants of mothers’ and children’s diets in Nigeria: an in-depth study of the 2018 Demographic and Health Survey - Nadia Akseer; Rebecca Heidkamp; Hana Tasic; Olutayo Adeyemi (BMJ Open)
Objectives Improving the diversity of the diets in young children 6–23 months is a policy priority in Nigeria and globally. Studying the relationship between maternal and child food group intake can provide valuable insights for stakeholders designing nutrition programmes in low-income and middle-income countries.Design We examined the relationship between maternal and child dietary diversity among 8975 mother–child pairs using the Nigeria 2018 Demographic and Health Survey (DHS). We assessed concordance and discordance between maternal and child food group intake using the McNemar’s χ2 test, and the determinants of child minimum dietary diversity (MDD-C) including women MDD (MDD-W) using hierarchical multivariable probit regression modelling.Setting Nigeria.Participants 8975 mother–child pairs from the Nigeria DHS.Primary and secondary outcome measures MDD-C, MDD-W, concordance and discordance in the food groups consumed by mothers and their children.Results MDD increased with age for both children and mothers. Grains, roots and tubers had high concordance in mother–child dyads (90%); discordance was highest for legumes and nuts (36%), flesh foods (26%), and fruits and vegetables (39% for vitamin-A rich and 57% for other). Consumption of animal source food (dairy, flesh foods, eggs) was higher for dyads with older mothers, educated mothers and more wealthy mothers. Maternal MDD-W was the strongest predictor of MDD-C in multivariable analyses (coef 0.27; 95% CI 0.25 to 0.29, p<0.000); socioeconomic indicators including wealth (p<0.000), mother’s education (p<0.000) were also statistically significant in multivariable analyses and rural residence (p<0.000) was statistically significant in bivariate analysis.Conclusion Programming to address child nutrition should be aimed at the mother–child dyad as their food consumption patterns are related and some food groups appear to be withheld from children. Stakeholders including governments, development partners, non-governmental organizations, donors and civil society can act on these findings in their efforts to address undernutrition in the global child population.